(untitled) (Archives of Clinical Psychiatry, 2008)
BACKGROUND: Maternal depression has been identified as a possibly harmful condition for child development, showing to be associated with emotional and behavioral difficulties. OBJECTIVES: To identify and analyze articles in the indexed literature addressing the impact of maternal depression for school-age children. METHODS: The procedure was made via the electronic databases Medline, Lilacs, Scielo, Index Psi, and Psyc Info, considering the production of the last five years (2002-2007). Thirty empirical articles were identified and analyzed. RESULTS: In the overall analysis, there was a similar distribution regarding the studies' design, characteristics of the samples and forms of assessment. Data collections were performed in different contexts with a variety of resources and informants. Maternal depression was linked to difficulties faced by children such as behavioral problems, depressive symptoms, and cognitive and social impairments, regardless of the time of first exposure to maternal depression and designs adopted. Such impairments were intensified by the presence of comorbidities. DISCUSSION: Maternal depression was configured as a risk factor for child development with a negative impact on school-age children. In terms of mental health, greater attention to children living side by side with this condition seems to be relevant, aimed at the early detection of any difficulties as a way to implement preventive practices.